ANALISIS SISTEM REKRUTMEN DAN SELEKSI DALAM MENINGKATKAN KUALITAS SDM DI PT. BINTANG SERAGAM INDONESIA TANGERANG SELATAN - Nafa Cahyani Agustin; Ahmad Nazir (Al Hasanah Barokah Foundation, 2026)
This study aims to analyze the recruitment and selection system to improve the quality of human resources at PT. Bintang Seragam Indonesia. The research method used descriptive qualitative techniques with interviews, observation, and documentation. The results show that the recruitment process includes identifying workforce needs, publishing vacancies, administrative selection, and testing and interviews. Selection emphasizes education, experience, skills, and work attitudes. In general, the implemented system is quite effective, but there are still weaknesses such as health checks and selection for strategic positions that are not optimal. The quality of human resources produced shows a difference between high- and low-performing employees. To address this, the company needs to improve selection standards by adding a more comprehensive health test stage and implementing written tests for all job positions, not just limited to the finance and content creative departments. With these improvements, the quality of human resources is expected to be more evenly distributed and able to support the improvement of company performance.